PENERAPAN METODE CAMEL DALAM PENILAIAN KONDISI KESEHATAN BANK UMUM PEMERINTAH DI INDONESIA - Panggabean, Priska Basariana (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The level of banking health shows the effectiveness of banks in carrying out their operational activities, activeness in maintaining financial stability and quality of service for customers. Bank Indonesia as the central bank, has a major role in monitoring and maintaining the quality and health of all banking institutions in Indonesia. The health condition of financial institutions can be evaluated using the CAMEL method, which is a measurement of Capital, Asset, Management, Earning and Liquidity. In this research, measurement, comparison and analysis of the health of government commercial banks in Indonesia were conducted based on published financial statement, with data from 2018 to 2022.